ANALISIS KUALITAS PELAYANAN,PEMERIKSAAN DAN PENAGIHAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KPP PRATAMA BATAM SELATAN - Purba, lusia dedi anita; Wage, Sunarto (LPPM Universitas Putera Batam, 2021)
This study aims to determine the analysis of the influence of service quality, inspection taxes collection on taxpayer compliance at KPP Pratama Batam Selatan. The population this study amounted 346,894 personal taxpayers, the sample was determined using slovin formula, which amounted to 400 taxpayers. Results of the partial test service quality obtained the t value -0.101 < 1.965 t table and significant value 0.920 > 0.05 which means that the service quality variable has no significant effect on taxpayer compliance,examination obtained t count value 4.262 > 1.965 t table and significant value 0.000 < 0.05, which means that the audit variable has significant effect against tax compliance , and tax collection obtained t value amounted to 10.691> 1.965 t table as well as significant value 0.000 <0.05, meaning that tax collection variables have significant effect on thetaxpayer compliance. The results of simultaneous test showed that value of service quality, tax audit and collection had significant effect on taxpayer compliance. The value of f arithmetic was 61.113 > 2.605 and significant value was 0.000 < 0.05. The results of determination test obtained value of 0.793 or 79.3%, meaning that there was an influence on the variables of service quality, audit and tax collection on taxpayer compliance of 79.3%. The remaining 20.7% is influenced by other variables that do not exist in this study .